2017
DOI: 10.1371/journal.pone.0169667
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Association of Land Management Preferences: Evidence from Family Forest Owners

Abstract: Individual behavior is influenced by factors intrinsic to the decision-maker but also associated with other individuals and their ownerships with such relationship intensified by geographic proximity. The land management literature is scarce in the spatially integrated analysis of biophysical and socio-economic data. Localized land management decisions are likely driven by spatially-explicit but often unobserved resource conditions, influenced by an individual’s own characteristics, proximal lands and fellow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
3
4
0
Order By: Relevance
“…Every 4 ha increase in land ownership raises the odds of harvest intentions by 1.5 (Figure 3). The direction of these results are consistent with prior FFO harvesting studies (e.g., Aguilar, Cai, & Butler, 2017;Silver et al, 2015).…”
Section: Mean Responsesupporting
confidence: 89%
See 1 more Smart Citation
“…Every 4 ha increase in land ownership raises the odds of harvest intentions by 1.5 (Figure 3). The direction of these results are consistent with prior FFO harvesting studies (e.g., Aguilar, Cai, & Butler, 2017;Silver et al, 2015).…”
Section: Mean Responsesupporting
confidence: 89%
“…Here, FFOs with physically close ties to their land (i.e., experience with and goals of timber production, objectives of woodland resource consumption, and resident owners) had the greatest likelihood of harvesting, consistent with extant studies (e.g., Aguilar et al, 2017;Molnar et al, 2007;Silver et al, 2015). Across the U.S., 22% of ownerships own their land for timber, 29% have cut experience with commercial cutting, 44% for own for consumption purposes, and 63% of the ownerships were non-absentee (Butler et al, 2016b).…”
Section: Discussionsupporting
confidence: 79%
“…Previous research on forest owners has examined determinants of management activities, such as harvesting, the management of insects and invasive species, climate change adaptation, wildlife practices, and participation in different programs (e.g., concerning conservation). Results have revealed that structural characteristics relating to the owner and the forest (e.g., gender, age, forest type, size of forest, and distance from roads) are associated with management activities (e.g., Joshi and Arano 2009 ; Lidestav and Berg Lejon 2013 ; Silver et al 2015 ; Coté et al 2016 ; Aguilar et al 2017 ; Thompson et al 2017 ; Floress et al 2019 ). In addition, social and psychological factors, such as social networks, personal experience, forest values and management objectives, subjective knowledge or awareness, and beliefs and attitudes have been found to be important for engagement in particular activities (Karppinen 2005 ; Joshi and Arano 2009 ; Blennow et al 2012 ; Hendee and Flint 2013 ; Thompson and Hansen 2013 ; Põllumäe et al 2014 ; Sagor and Becker 2014 ; Drescher et al 2017 ; Kelly et al 2017 ; Eriksson 2017 , 2018b ; Vulturius et al 2018 ; Fischer 2019 ; Thorn et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The shifting characteristics of forest ownership, documented in a number of previous studies (e.g. Berlin et al 2006;Ingemarson et al 2006;Nordlund and Westin 2011;Haugen et al 2016;Aguilar et al 2017;Butler et al 2017;Keskitalo 2017), constitute one of the vital drivers in this transition. Both distance and knowledge are emphasized as the main challenges, but the increasingly changing behaviour and heterogeneity of forest owners also contributes to reshaping the sales interaction and the integration of services.…”
Section: Discussionmentioning
confidence: 93%